Analisis Filosofis terhadap Fatwa DSN MUI No. 106 Tahun 2016 tentang Wakaf Manfaat Asuransi dan Manfaat Investasi pada Asuransi Jiwa Syari’ah - Endang Sriani; Abu Hapsin (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2021)
The purpose of this study is to explore the essence, substance and benefits of the DSN-MUI fatwa no.  106 of  2016 concerning waqf insurance benefits and investment benefits in Sharia Life insurance.  This is a library research with primary law, DSN-MUI fatwa no. 106 of  2016. A philosophical approach was chosen in this study to describe the ontology, epistemology and axiology aspects of the fatwa.  The results of this study indicate that the essence of the fatwa is to accommodate legal needs in the synergy of waqf and sharia insurance in order to maximize the benefits of waqf and sharia insurance for the wider community.